Muscle‐derived matrix metalloproteinase regulates stem cell proliferation in planarians. Issue 9 (28th July 2016) - Dingwall, Caitlin B.; King, Ryan S.
Abstract : Background : Matrix metalloproteinases (MMPs) are a large family of regulatory enzymes that function in extracellular matrix degradation and facilitate a diverse range of cellular processes. Despite the significant focus on the activities of MMPs in human disease, there is a lack of substantial knowledge regarding their normal physiological roles and their role in regulating aspects of stem cell biology. The freshwater planarian Schmidtea mediterranea ( S. mediterranea ) is an excellent system in which to study robust and nearly unlimited regeneration, guided by a population of mitotically active stem cells, termed neoblasts.Results : We characterized MMPs in the context of planarian stem cells, specifically exploring the role of S. mediterranea MT‐MMPB. Using in situ hybridization and available functional genomic tools, we observed that mt‐mmpB is expressed in the dorsoventral muscle cells, and its loss results in a reduction in animal size accompanied by a decrease in mitotic cells, suggesting that it plays a unique role in regulating stem cell proliferation.Conclusions : The novel findings of this study bring to light the unique and critical roles that muscles play in regulating neoblast function, and more broadly, highlight the importance of MMPs in stem cell biology. Developmental Dynamics 245:963–970, 2016 . © 2016 Wiley Periodicals, Inc.